2021
DOI: 10.1177/1120672121999991
|View full text |Cite
|
Sign up to set email alerts
|

Astigmatism correction with toric implantable collamer lens in low and high astigmatism groups

Abstract: Purpose: To analyze the target induced astigmatism (TIA), surgically induced astigmatism (SIA), difference vector (DV), and correction index (CI) in the correction of astigmatism with phakic lenses, and its influence on visual acuity, and to analyze the safety and efficacy indexes of the correction of high and low power astigmatism with toric phakic lenses. Design: Retrospective comparative study. Methods: The medical records of patients that were operated on at the research center during the period were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This is in line with the results described by Cano-Ortiz et al in their recent publication on low power astigmatism correction with TICL lenses. 33 In their article, Cano indicates a mean preop power of −1.50D Cyl, which is in line with our preop data. They obtained a cylinder correction accuracy equivalent to ours (R 2 = 0.942) confirming the stability and predictability of the procedure.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is in line with the results described by Cano-Ortiz et al in their recent publication on low power astigmatism correction with TICL lenses. 33 In their article, Cano indicates a mean preop power of −1.50D Cyl, which is in line with our preop data. They obtained a cylinder correction accuracy equivalent to ours (R 2 = 0.942) confirming the stability and predictability of the procedure.…”
Section: Discussionsupporting
confidence: 87%
“…At one month, mean vault was 573. 33 Mean IOP did not suffer significant changes in the follow-up, and the difference between preop IOP and IOP after 12 months did not show statistical significance (p = 0.587).…”
Section: Resultsmentioning
confidence: 83%
“… 42 , 43 In patients with astigmatism, toric ICLs yielded promising results in correcting astigmatic component and were even more effective in eyes with high astigmatism (≥2 D and ≤4 D) than in those with low astigmatism (≥0.75 D and <2 D). 44 , 45 In a review of data from 1905 eyes by Packer in 2018, the weighted average efficacy index was 1.04 (range, 0.90–1.35) and weighted average postoperative uncorrected distance visual acuity (UDVA) was 20/19 (logMAR −0.02) (range, 20/12–20/27 (logMAR −0.20 to 0.14)), confirming the good refractive outcomes of the ICL. 46 In a recent US-FDA clinical trial evaluating 629 eyes of 327 participants, EVO ICL lenses achieved high levels of UDVA (−0.059 ± 0.10 logMAR), with an efficacy index of 1.06.…”
Section: Resultsmentioning
confidence: 99%
“…42 However, compared with patients with high astigmatism (≥2 D and ≤4 D), patients with low astigmatism (≥0.75 D and <2 D) showed slightly lower SE and percentage of eyes having cylinder rotation within 5°. 44 The literature published between October 2018 and October 2022 reporting predictability of refractive correction expressed as percentages within 0.5 D and 1.0 D of target is summarized in Table 2. The pooled data of over 3000 eyes are also shown in the table.…”
Section: Refractive Predictabilitymentioning
confidence: 99%
“…Previous studies have found that higher vault tends to have hyperopia and lower vault tends to have myopia [ 14 16 ]. Others have also reported that postoperative refractive outcome after ICL implantation depends on preoperative refraction [ 17 19 ]. Therefore, the more accurate lens power step may help improve the accuracy of refractive correction.…”
Section: Introductionmentioning
confidence: 99%